2021
DOI: 10.1007/s12134-021-00817-1
|View full text |Cite
|
Sign up to set email alerts
|

Social Capital and Its Effect on Labour Market (Mis)match: Migrants’ Overqualification in Germany

Abstract: If a person is overqualified in the sense that an employee’s level of training exceeds the job requirements, then some human capital lies idle and cannot be converted into appropriate (monetary and non-monetary) returns. Migrants are particularly at risk of being overqualified in their employment; however, this phenomenon cannot be fully explained by differences in human capital or socio-economic characteristics. This paper examines whether social capital plays a decisive role in migrants’ risk of overqualific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 82 publications
(92 reference statements)
0
8
0
2
Order By: Relevance
“…Considerando a teoria de ajustamento da pessoa ao ambiente, quando os funcionários identificam um desajuste ao nível das oportunidades e das ofertas, aqueles em sobrequalificação percebida estarão mais sujeitos à frustração (Erdogan et al, 2011a), o que pode potencialmente gerar mais sentimentos negativos (Yu et al, 2019) às suas qualificações (Kracke & Klug, 2021). Os resultados também sugerem que estes imigrantes se identificam menos com o país de acolhimento, expressando uma maior vontade de sair de Portugal, o que pode ser resultado de as redes dos imigrantes brasileiros em Portugal, não serem redes apoiantes, predominando a desconfiança e a competição (Padilla, 2006).…”
Section: Discussionunclassified
“…Considerando a teoria de ajustamento da pessoa ao ambiente, quando os funcionários identificam um desajuste ao nível das oportunidades e das ofertas, aqueles em sobrequalificação percebida estarão mais sujeitos à frustração (Erdogan et al, 2011a), o que pode potencialmente gerar mais sentimentos negativos (Yu et al, 2019) às suas qualificações (Kracke & Klug, 2021). Os resultados também sugerem que estes imigrantes se identificam menos com o país de acolhimento, expressando uma maior vontade de sair de Portugal, o que pode ser resultado de as redes dos imigrantes brasileiros em Portugal, não serem redes apoiantes, predominando a desconfiança e a competição (Padilla, 2006).…”
Section: Discussionunclassified
“…Empirical research with this focus has for example, shown that immigrants using informal job search methods have worse labour market outcomes than comparable natives, interpreted as happening because of the immigrants' lower amounts of social capital (Behtoui, 2008;Kracke & Klug, 2021). It is also common to differentiate between social contacts with other co-ethnics or other immigrants, and social contacts with natives, i.e., between bonding and bridging social capital.…”
Section: Explaining Immigrants' Labour Market Situationmentioning
confidence: 99%
“…Moreover, labour market integration is sometimes prevented by the societal context, including different forms of 'othering' (ranging from the stereotyping of migrants to racism or discriminatory behaviours) that discourage newcomers from working or that expose them to exploitation and harassment in their workplace (C ˇane ˇk, 2016; Greenspan et al, 2018). Furthermore, given the important role that social connections still play for people finding employment in Europe, the lack of social capital (or the reliance upon primarily an ethnic-bonding cluster of social interactions) might also prevent migrants from finding decent jobs (Aguilera, 2002;Kracke & Klug, 2021).…”
Section: Migrants' Labour Market Barriers and Csosmentioning
confidence: 99%